Working Environment And Loyalty Link With Performance Behavior - Adiwati, Lia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
In plain view, you can see the tendency of work behavior, because attitudes and behavior are influenced by personality factors. In addition, external factors such as the environment also have an influence on a person's perspective and emotions, the better the response of the work environment, the more positive attitude and behavior patterns can be encouraged. Based on this, this research actually aims to look at changes in positive work behavior (performance) in employees in terms of environmental factors and loyalty. This research is based on the characteristics of positivism research, in which the proof depends on numerical data. In the process of analysis used regression techniques with the application of Partial Least Square. The research sample is 80 people with a number of criteria in its determination. The results of the study show that performance behavior is influenced by internal (personality, competence, integrity, etc.) and external (work environment, leadership, organizational support, etc.) factors, in this study, work environment and loyalty. Loyalty is a characteristic of someone who is responsible for the duties/positions they carry out, so that in carrying out their duties they will always try their best. Likewise with the work environment, an employee will work more actively if he has co-workers who support and motivate each other